Determinants of zakah (Islamic tax) compliance behavior. Issue 2 (19th August 2014) - Saad, Ram Al Jaffri; Haniffa, Roszaini
Abstract : Purpose: The purpose of the study was to examine factors influencing business zakah compliance behavior. Design/methodology/approach: The theory of reasoned action (TRA) was adopted to investigate whether attitude, subjective norm and intention were the determinants of zakah compliance behavior based on questionnaire survey of 227 active businessmen in one district in Malaysia. Findings: Results indicate intention to be a significant predictor for zakah compliance behavior. Intention is further found to be influenced by both attitude and subjective norm and it mediates the relationship between both factors with business zakah compliance behavior. Practical implications: Since attitude, subjective norm and intention are found to influence business zakah compliance behavior, zakah institutions should give serious attention on these factors to improve their zakah collection in the future. Originality/value: The study supports the argument that in a loosely regulated environment like zakah, the theory of reasoned action can still effectively explain the behavior of zakah compliance.